Designing game-based learning kit with integration of augmented reality for learning geography - Ong, Ace Hong; Abd Halim, Noor Dayana; Zulkifli, Nurul Nadwa; Jumaat, Nurul Farhana; Mohd Zaid, Norasykin; Mokhtar, Mahani (International Association of Online Engineering (IAOE), 2022)
The development of education is changing in line with the development of current technology, and these developments have influenced many innovations in teaching and learning methods. Many technology-based games have been introduced in the market; however, not all games are suitable for student learning. This is because the features of a game must have an impact on education; it is essential to choose a game based on appropriate criteria for education. Therefore, this paper describes the integration process of game-based learning features outlined by Alaswad and Nadolny (2015), which are goal, interaction and feedback. The three features are designed in a learning kit called the “Kit Pengembara” for learning the topic of “Arah Mata Angin” and “Bearing Sudutan”, the subject of Geography Form 1. In addition, this Kit Pengembara also integrates the UniteAR application for user to complete a given task using augmented reality. Therefore, this paper can provide an overview to educators in the form of their educational innovations that integrate technology to increase student engagement.